Outcome of pure mucocele‐like lesions diagnosed on breast core biopsy. Issue 6 (12th February 2013) - Rakha, Emad A; Shaaban, Abeer M; Haider, Syeda Asma; Jenkins, Jacquie; Menon, Sindhu; Johnson, Christopher; Yamaguchi, Rin; Murphy, Alison; Liston, Joyce; Cornford, Eleanor; Hamilton, Lisa; James, Jonathan; et al.
<x xml:space="preserve">Abstract</x> Aim Current guidelines recommend that mucocele‐like lesions (MLL) of the breast diagnosed on needle core biopsy (NCB) should be categorized as a lesion of uncertain malignant potential (B3). However, data on the outcome of MLL diagnosed on NCB remains limited due to the rarity of this lesion. The aim of this study was to assess the outcome of pure MLL without atypia diagnosed on NCB using a large series of cases and a review of the literature to provide evidence that can guide management. Methods and results Patients who underwent diagnostic excision biopsy after a core biopsy diagnosis of MLL without atypia were identified from several centres. Two of 54 patients (4%) with MLL without atypia on core biopsy had ductal carcinoma in situ in the subsequent excision specimen. This is similar to the rate in previous studies of 4% (four of 106). If there is atypia in the core biopsy, previous studies found that the frequency of malignancy is much higher at 21% (seven of 33). Conclusions Our results provide evidence that pure MLL without atypia diagnosed on NCB is usually associated with a benign outcome.